Clinical and biochemical studies on treatment of Lesch-Nyhan syndrome - Watts, R. W. E. (1974)
The clinical findings in a previously unreported case of the Lesch-Nyhan syndrome are described. Though formal intellectual testing is very difficult because of the severe choreoathetosis and compulsive self mutilation, cognition appears to be less severely damaged than motor functions. It is most important to devise an active education programme for these children, and to control their self mutilation. Extracting all the teeth is strongly recommended from the latter point of view. Replacing the deficient enzyme by means of exchange blood transfusion was associated with only a transient and small decrease of the serum uric acid level; the urinary uric acid excretion was not significantly altered. The blood levels of hypoxanthine-guanine phosphoribosyltransferase (HGPRT) had not decreased to about 10% of the mean normal range until 90 days after the transfusion. The patient's motor state was not improved by any of the following. (i) Exchange blood transfusion; (ii) oral adenine and allopurinol; (iii) tetrabenazine; (iv) thiopropazate; (v) chlorpromazine. His scores in the Reynell Development Language scale tests improved during the 14-month period of observation, but the present evidence does not justify attributing this to any of the attempted treatments. Some possible reasons for the apparent failure of transfusion to suppress purine synthesis or to improve the neurological disorder are discussed. The present clear evidence that HGPRT-containing cells remain in the circulation in sufficient numbers to keep the HGPRT activity above 10% of the normal value for at least 90 days, suggests that it would still be justifiable to investigate a similar treatment in the neonatal period.